Irradiation dose does not affect male reproductive organ size, sperm storage, and female remating propensity in Ceratitis capitata. Issue 1 (3rd February 2021) - Abraham, S.; Díaz, V.; Moyano, A.; Castillo, G.; Rull, J.; Suárez, L.; Murúa, A.F.; Pantano, V.; Molina, D.; Ovruski, S.M.
Abstract: The Mediterranean fruit fly Ceratitis capitata is a globally invasive pest, often controlled with the sterile insect technique (SIT). For the SIT, mass-rearing of the target insect followed by irradiation are imperatives. Sterile males are often less able to inhibit female remating and transfer less number of sperm, and even irradiation could affect male reproductive organs, with consequences for their ability to inhibit female remating. On the other hand, male age could affect their ability to modulate female response after mating. Here, we evaluated the quality of the genetic sexing strain Vienna-8-tsl mass-reared in Bioplanta San Juan, Argentina, under laboratory conditions, with regard to: (i) the ability of sterile males irradiated at 100 or 140 Gy to inhibit female remating, in the same day and at 24 h of first copulation; (ii) the ability of 3, 4 or 5 day-old sterile males to inhibit female remating at 24 h of first copulation, and (iii) the effect of a reduction in irradiation doses on the number of sperm stored by females and reproductive organ size in virgin males. Sterile males were better able than wild males to inhibit female remating in the same day of first copulation and as able as wild males 1 day after first copulation. Male age did not affect their ability to inhibit female receptivity. Number of sperm stored by females, testes size and ectodermal accessory glands size were not affected by male identity, while sterile 100 Gy males had larger mesodermal accessory glands than control lab males. A reduction in irradiation dose does not impact any variable measured, except for percentage of sperm-depleted females: females mated with sterile 100 Gy males had lower probabilities to store sperm. The results showed here are very encouraging for tsl Vienna 8 strain reared in Argentina and are discussed in comparison with previous studies in C. capitata female remating with dissimilar results.